2022
DOI: 10.3390/pharmaceutics14061174
|View full text |Cite
|
Sign up to set email alerts
|

The Release of a Highly Cytotoxic Paullone Bearing a TEMPO Free Radical from the HSA Hydrogel: An EPR Spectroscopic Characterization

Abstract: This study shows the potential of a thermally induced human serum albumin (HSA) hydrogel to serve as a drug depot for sustained release of a highly cytotoxic modified paullone ligand bearing a TEMPO free radical (HL). The binding of HL to HSA was studied by electron paramagnetic resonance (EPR) spectroscopy and imaging. The EPR protocol was also implemented for the study of matrix degradation, and ligand diffusion rate, in two additional spin-labeled hydrogels, containing 5-doxylstearate and 3-carbamoyl-proxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…It was determined that the diffusion kinetics are the same for both spin probes, resulting in ~1% spin probe content in the OVA hydrogels after 1 h (Figure 3). This is in agreement with the result obtained for the release of 96% 3CP from the 30 wt% HSA hydrogel after 1 h [38], showing that the diffusion of hydrophilic molecules, which do not bind to the protein matrix, from OVA and HSA hydrogels, occurs on the same time scale. In this context, since it has been shown that the diffusion of the entrapped molecule throughout the hydrogel depends on the relative size of the molecule compared to that of the water pore [19,51,52], it may be concluded that the water pores of the supramolecular OVA and HSA hydrogels are larger than 3CP and 3CxP molecules, resulting in diffusion-dominated release of small probes from both hydrogel types [19].…”
Section: The Release Of Hydrophilic Spin Probes 3cp and 3cxp From Ova...supporting
confidence: 92%
See 2 more Smart Citations
“…It was determined that the diffusion kinetics are the same for both spin probes, resulting in ~1% spin probe content in the OVA hydrogels after 1 h (Figure 3). This is in agreement with the result obtained for the release of 96% 3CP from the 30 wt% HSA hydrogel after 1 h [38], showing that the diffusion of hydrophilic molecules, which do not bind to the protein matrix, from OVA and HSA hydrogels, occurs on the same time scale. In this context, since it has been shown that the diffusion of the entrapped molecule throughout the hydrogel depends on the relative size of the molecule compared to that of the water pore [19,51,52], it may be concluded that the water pores of the supramolecular OVA and HSA hydrogels are larger than 3CP and 3CxP molecules, resulting in diffusion-dominated release of small probes from both hydrogel types [19].…”
Section: The Release Of Hydrophilic Spin Probes 3cp and 3cxp From Ova...supporting
confidence: 92%
“…In this context, since it has been shown that the diffusion of the entrapped molecule throughout the hydrogel depends on the relative size of the molecule compared to that of the water pore [19,51,52], it may be concluded that the water pores of the supramolecular OVA and HSA hydrogels are larger than 3CP and 3CxP molecules, resulting in diffusion-dominated release of small probes from both hydrogel types [19]. It is worthy pointing out that the macroscopic appearance of the OVA hydrogels had changed upon incubation in physiological saline from transparent to opaque white (Figure S3), which has not been previously observed for HSA hydrogels [38]. Moreover, the study on PC(HEW) [35] has reported that upon immersion in water, the ionic surfactant-modified hen egg-white protein condensate hydrogels change their appearance from clear to opaque, which has been attributed to the regeneration of the non-covalent gel network.…”
Section: The Release Of Hydrophilic Spin Probes 3cp and 3cxp From Ova...mentioning
confidence: 60%
See 1 more Smart Citation
“…A BSA-based conductive hydrogel prepared by physical cross-linking has excellent mechanical properties (1.61 MPa elastic modulus, 17.66 MJ/m 3 toughness, and 5.36 MPa tensile stress) and shows good promise for biomedical applications (Xu et al, 2023) High surface hydrophobicity The fibrillation process often involves the unfolding of the internal structure of the protein, leading to the exposure of more hydrophobic amino acids (Mohammadian et al, 2019;Zhou et al, 2020). The HSA hydrogel was constructed by Ana et al, which has a good hydrophobic drug-binding pocket and can be loaded with various substances (especially for hydrophobic drugs) (Vesković et al, 2022) Controlled flexibility Nanofibers with different flexibility, including flexible, semi-flexible and rigid dimensions, can be prepared by simply adjusting the fibrillation conditions, such as pH, ionic strength, protein concentration, etc (Cao and Mezzenga, 2019;Jirkovec et al, 2021). Injectable redox albumin-based hydrogel with in-situ loaded dihydromyricetin constructed by Deng et al, which shows excellent self-healing property, elasticity and biocompatibility and can be used for drug delivery (such as dihydromyricetin) (Deng et al, 2022) Chemical properties Highly tolerant of the environment Compared to protein monomers, amyloid fibrils are more tolerant of extreme environments such as acid, heat and enzymes.…”
Section: Specific Properties Descriptionmentioning
confidence: 99%
“…HSA-based hydrogels are often found in the applications of drug delivery because of the multiple drug-binding sites they possess. Vesković et al constructed a hydrogel drug-depot using HSA, which can be used for sustained release of a highly cytotoxic modified paullone ligand bearing a TEMPO free radical (HL), so it demonstrated excellent drug-delivery potential ( Vesković et al, 2022 ). In 2014, a hydrogel constructed from HSA by Gao et al, which can effectively carry hydrophobic drugs such as ibuprofen, paclitaxel and dexamethasone.…”
Section: Hydrogels Based On Different Types Of Albuminmentioning
confidence: 99%